X-ray crystal structure of the Escherichia coli RadD DNA repair protein bound to ADP reveals a novel zinc ribbon domain - Osorio Garcia, Miguel A.; Satyshur, Kenneth A.; Cox, Michael M.; Keck, James L. (PLOS ONE, 2022)
Genome maintenance is an essential process in all cells. In prokaryotes, the RadD protein is important for survival under conditions that include DNA-damaging radiation. Precisely how RadD participates in genome maintenance remains unclear. Here we present a high-resolution X-ray crystal structure of ADP-bound Escherichia coli RadD, revealing a zinc-ribbon element that was not modelled in a previous RadD crystal structure. Insights into the mode of nucleotide binding and additional structure refinement afforded by the new RadD model will help to drive investigations into the activity of RadD as a genome stability and repair factor.